(untitled) (Global Journal of Management and Business Research, 2023)
In the current economic scenario and post-pandemic business resumption the companies are pressed to look for efficient alternatives that reduce costs and provide productive wins The lean philosophy as well as its organizational improvement methodology is a powerful factor in improving processes identifying waste and increasing productivity and efficiency in the productive chain The lean manufacturing has the purpose of identifying and eliminating waste and looking for perfection in the products always focusing on the client s vision This work was carried out in a metallurgical company and had as its main objective to analyze the impact of the lean philosophy in the company and identify the benefits provided by process improvement applications in a medium-sized enterprise This work used the action research method which collected information and processes analysis directly in the factory environment for the subsequent development of strategies and improvement plans